Research culture: An indispensible practice for progress? - Idrus, Faizah; Ismail, Nik Ahmad Hisham; Hussien, Suhailah; Mamat, Arifin; Che Haron, Sueraya (2014)
One of the major responsibilities of higher educational institutions is to imbue in academic staff and students the passion to carry out research. Equally, for any institutions to be progressive, both students and academic staff must possess the zeal for continuous research practice. The question here lies within the boundaries of research practices of the academic staff and students themselves, which then underpins the ‘status’ of that particular institution in the so-called academic ranking. Thus, the purpose of this investigation is to ascertain as to whether there is actually a ‘research culture’ at The International Islamic University Malaysia (IIUM) in its quest to being conferred a Research University status. Is research culture an obligatory measure to be able to produce research products and publications? Therefore in order to be able to answer this fundamental question, a parallel combination mixed method approach has been carried out with eight Heads of Research (HOR) and two postgraduate students (PG) respectively across eight kulliyah (faculty). A combination of in-depth interviews with HORs and PG students as well as and a set of questionnaire was distributed to 411 academic staff across 3 campuses to seek answers to research questions. Descriptive statistics, SEM and thematic analyses were carried out to analyse the data. The findings point to the direction of a clear absence of research culture amongst academic staff and postgraduate students as a whole at this university. Suggestions were recommended to the university authority and management to tackle several fundamental issues regarding research practices which should be dealt with swiftly.